Fine-scale mapping of heat-hazard risk and vulnerability using geo-spatial techniques: Insights from a tropical Indian city - Kotharkar Rajashree; Ghosh Aveek; Keskar Ravindra (Geographica Pannonica)
Unprecedented extreme heat events (EHEs) have amplified associated health risks, but they present great differences within the urban environment. This paper aims to assess heat-hazard risk (HHR) and associated vulnerability in Nagpur, a heat-prone Indian city using remotely sensed and on-site meteorological data. HHR was generated through high resolution local climate zone (LCZ) maps via the product of hazard and vulnerability which featured census-tract socio-economic variables (sensitivity and adaptive capacity) and exposure. Principal component analysis (PCA) with equal weighting was applied to develop a composite fine-scale heat vulnerability index (HVI). Out of 136 wards, a total of 68 wards were identified to have 'high' or 'very high' HVI featuring about 49.06% of the population. LCZ-based spatial mapping showed a heterogeneous heat 'risk-scape' across the city. 'High' and 'very high' heat vulnerability/risk (HV/R) signature was observed in city core, its adjoining areas (LCZs 3 and 3F) and urban fringes (LCZs 9 and 93). Conversely, open areas with moderate vegetation cover and natural classes (LCZs 6, 6B, A and B) showed 'moderate' to 'low' HHR. The findings of this research will enable the urban practitioners and policymakers to deal with explicit determinants of heat vulnerability and risk especially in regions with low adaptive capacity.